The Kalman Filter Performance for Dynamic Change in System Parameters - Hisham Alrawashdeh; Johnson A Sumadu (Institute of Advanced Engineering and Science, 2013)
This paper studies the performance of the simple kalman filter for dynamic changes of the system variables. The kalman filter was used to detect the fundamental component of power system signal contained harmonics. First the performance of the kalman filter was examined for a sudden change in the amplitude of the fundamental component, then for a frequency variation. The noise covariance matrices were assumed to be unknown, the values of these matrices were changed to study the.DOI:http://dx.doi.org/10.11591/ijece.v3i6.3857